Supporting Science Teachers’ Learner-Centered Technology Integration through Situated Mentoring - Marian G. Rosenberg; Yunjo An (Educational Process: International Journal)
Learner-centered technology integration is a challenging task for many teachers. In an attempt to support science teachers’ learner-centered technology integration efforts, this study developed a situated mentoring program and examined its impact on teachers’ attitudes, technology integration practices, and perceived barriers. Further, the study explored ways to improve the situated mentoring program. Qualitative data were collected from pre-mentoring interviews, observations, and post-mentoring interviews. The results revealed that most participants were teacher-centered and somewhat skeptical about the value of technology for learning prior to the mentoring program. The situated mentoring program had a positive effect on the participants’ attitudes toward learner-centered technology integration. However, in terms of changes in technology integration practices, the results were mixed and varied from teacher to teacher. The personalized professional development and support appeared to be one of the major strengths of the situated mentoring program. Findings from the participants’ program evaluation data provide useful insights into professional development for learner-centered technology integration.